Characterization Of Plastid Genome Of A Medicinal Plant Capparis Decidua (Forsk) Edgew (Applied Biological Research, 2022)
Capparis decidua is one of the important medicinal plants belonging to the  family Capparaceae. The complete plastid genome of C. decidua, which is  157,573 bp long, was examined. In this study, we analyzed the complete plastid genome of species using high-throughput sequencing technology  and assembled using NOVOPlasty. The large single copy (LSC), small  single copy (SSC) and inverted repeats (IRa and IRb) were 85950, 18621  and 26526 bp long. There were 136 genes in the genome: 80 protein-coding  genes, 31 tRNA genes, and 4 rRNA genes. The repeat sequences findings  showed that chloroplast genome contained a variety of repeats, with  palindromic repeat occurring more frequently. A set of 279 SSR were  mined from the C. decidua genome and most of them possess  mononucleotide repeat motifs (A/T).
Keywords: Capparis decidua; chloroplast genome; genes; plastid; SSR